Polymorphous low grade adenocarcinoma of the parotid gland: A case report with cytohistological correlation and its immunohistochemical study - S Shrestha; CB Pun; R Basyal; T Pathak; S Bastola; S Neupane; MC Lee (Association of Clinical Pathologists of Nepal, 2012)
Polymorphous low-grade adenocarcinoma is a rare salivary gland malignant tumor of low aggressiveness, commonly occurring in minor salivary glands. Its origin in major salivary glands is considered exceedingly rare. We report a case of polymorphous low grade adenocarcinoma arising from left parotid in a 21-yearold female patient. Journal of Pathology of Nepal (2012) Vol. 2, 331-334 DOI: http://dx.doi.org/10.3126/jpn.v2i4.6890